2023
DOI: 10.3389/fcell.2023.1073805
|View full text |Cite
|
Sign up to set email alerts
|

GJB4 variants linked to skin disease exhibit a trafficking deficiency en route to gap junction formation that can be restored by co-expression of select connexins

Abstract: Epidermal keratinocytes are enriched with at least nine connexins that are key regulators of epidermal homeostasis. The role of Cx30.3 in keratinocytes and epidermal health became evident when fourteen autosomal dominant mutations in the Cx30.3-encoding GJB4 gene were linked to a rare and incurable skin disorder called erythrokeratodermia variabilis et progressiva (EKVP). While these variants are linked to EKVP, they remain largely uncharacterized hindering therapeutic options. In this study, we characterize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 105 publications
1
4
0
Order By: Relevance
“…This mutation significantly reduced Cx30.3 expression in the patient's epidermis, and consistent with this, the mutant protein displayed reduced expression and a more diffuse distribution compared to the membrane-localized wild-type Cx30.3 in HeLa cells (Zhang et al, 2022). Similarly, Cx30.3-G12D, Cx30.3-T85P, and Cx30.3-F189Y mutant proteins remained within the ER and exhibited impaired transport to the plasma membrane in rat epidermal keratinocytes (Lucaciu et al, 2023). Interestingly, these mutant protein-expressing cells also exhibited increased propidium iodide uptake, potentially indicating the presence of active hemichannels.…”
Section: Skin Diseases Caused By Cx31 and Cx303 Gene Mutationssupporting
confidence: 67%
See 2 more Smart Citations
“…This mutation significantly reduced Cx30.3 expression in the patient's epidermis, and consistent with this, the mutant protein displayed reduced expression and a more diffuse distribution compared to the membrane-localized wild-type Cx30.3 in HeLa cells (Zhang et al, 2022). Similarly, Cx30.3-G12D, Cx30.3-T85P, and Cx30.3-F189Y mutant proteins remained within the ER and exhibited impaired transport to the plasma membrane in rat epidermal keratinocytes (Lucaciu et al, 2023). Interestingly, these mutant protein-expressing cells also exhibited increased propidium iodide uptake, potentially indicating the presence of active hemichannels.…”
Section: Skin Diseases Caused By Cx31 and Cx303 Gene Mutationssupporting
confidence: 67%
“…Notably, co-expression of either wild-type Cx30.3 or other skin connexins (Cx26, Cx30, and Cx43) with Cx30.3 mutants facilitated the incorporation of mutant proteins into GJ at the plasma membrane. This finding suggests that upregulation of wild-type connexins in the epidermis may hold therapeutic potential for Cx30.3-related EKVP (Lucaciu et al, 2023).…”
Section: Skin Diseases Caused By Cx31 and Cx303 Gene Mutationsmentioning
confidence: 78%
See 1 more Smart Citation
“…Cx43 interacting with β-connexins is not without precedent, as Cx30.3 and mutant Cx26 (H73R or S183F) have been found to bind Cx43 in Cos7 cells and Xenopus oocytes, respectively ( Okamoto et al, 2020 ; Shuja et al, 2016 ). Furthermore, we have recently shown that Cx43 can intermix into the same gap junctions with Cx30.3 and Cx30.3 variants (G12D, T85P and F189Y) in keratinocytes ( Lucaciu et al, 2023a ). Next, we investigated Cx26, Cx30.3 and Cx31 as potential connexins that could rescue the cell surface delivery of Cx31.1 as they are likely to be expressed within the same keratinocyte and epidermal strata in a healthy epidermis ( Aasen and Kelsell, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…This raises questions regarding whether these selective interactions with Cx31.1 have pathological implications. Notably, various gain- and/or loss-of-function mutations in five connexins (Cx26, Cx30, Cx30.3, Cx31 and Cx43) have been linked to a variety of congenital skin diseases ( Scott et al, 2012 ; Sellitto et al, 2021 ; Lucaciu et al, 2023a ). As such, it is possible that mutations within these distinct connexin isoforms alter interactions with Cx31.1, which might explain the clinical variability of disease presentation.…”
Section: Discussionmentioning
confidence: 99%